2007
DOI: 10.1159/000096932
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fibrin Sealant in Hypospadias Surgical Repair Reduces the Frequency of Postoperative Complications

Abstract: Introduction: Urethrocutaneous fistulas (UCF) and flap dehiscence (FD) are the most common postoperative complications after hypospadias (HS) surgical repair. The aim of this study was to evaluate whether the application of fibrin sealant over the site of surgery and suture lines reduces these complications. Materials and Methods: A prospective cohort of consecutive patients was treated over a 3-year period. 30 patients were submitted to HS surgical repair plus application of fibrin glue over the suture line a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…The authors clearly demonstrated a shortened overall operative time and a decreased occurrence of the early postoperative leakage. Others however have pointed out that the application of glue in hypospadias repair does not completely eliminate fistula formation, even though it seems that it may minimizes the incidence of fistula formation and flap dehiscence [11,12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors clearly demonstrated a shortened overall operative time and a decreased occurrence of the early postoperative leakage. Others however have pointed out that the application of glue in hypospadias repair does not completely eliminate fistula formation, even though it seems that it may minimizes the incidence of fistula formation and flap dehiscence [11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated that covering the first suture line with single or double dartos flap or spongioplasty may decrease the incidence of fistula development [5,6,7,8,9]. Others have demonstrated some benefits with the use of fibrin glue as a sealant for urethrocutaneous fistula prevention after hypospadias repair and for the closure of fistulas [10,11,12]. However fibrin sealants from a single-donor or multiple donors have some risks of HCV, HBV or HIV contamination, may sometimes lead to a severe allergic reaction, and are also expensive [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They found out that the rate of fistula formation, postoperative edema and duration of hospitalization were all reduced using Tisseel, the commercially available fibrin glue, on suture lines [5]. Other studies have confirmed the reduction in the incidence of postoperative urethrocutaneous fistula using fibrin glue [17,18]. Fibrin sealants can also be useful in complex anterior and posterior urethral surgeries, when skin or buccal mucosal grafts are used.…”
Section: Discussionmentioning
confidence: 99%
“…Hick and Morey [13] used fibrin glue as a sealant to enhance wound healing in penile urethroplasty. Ambriz-González et al [14] concluded that the incidence of urethrocutaneous fistula after hypospadias surgical repair can be reduced by applying fibrin sealant over the site of surgery and the suture lines. Barbagli et al [4] used fibrin glue in bulbar urethroplasty and stated that the use of fibrin glue represents a slight but significant step toward perfecting the surgical technique of bulbar urethral reconstruction using dorsal buccal mucosal graft.…”
Section: Discussionmentioning
confidence: 99%